CONTEXTUAL TEACHING AND LEARNING-BASED TEACHING MATERIALS TO IMPROVE FINANCIAL LITERACY AMONG ELEMENTARY SCHOOL STUDENTS - Fitra Ramadhan; Mela Darmayanti; Non Dwishiera Cahya Anasta Shiera (Universitas Islam Negeri Mataram, 2025)
This study was motivated by the fact that fourth-grade elementary school students often have difficulty understanding the concepts of needs and wants, as well as the value of currency and its functions. The purpose of this study was to develop teaching materials based on Contextual Teaching and Learning (CTL) for fourth-grade elementary school students. The methodology used in this development is the Design and Development (D&D) model with the ADDIE approach, which includes: (1) Analyze, analyzing students' needs, learning outcomes, financial literacy indicators, materials, and the CTL approach; (2) Design, designing the initial teaching materials and creating a validation questionnaire; (3) Development, developing the design into a complete teaching material, conducting validation, and revising the teaching material; (4) Implementation, testing the teaching material on students; and (5) Evaluation, reflecting on the success of the teaching material. Data collection techniques in this study used questionnaires and tests. The data analysis techniques used were qualitative and quantitative. The teaching materials were organised into two parts: needs and desires (KEKIN), and understanding the value of currency and its functions (UANG PINTAR). The research results indicate that the instructional materials received a validation rating in the “Highly Suitable” category. Students' financial literacy improved significantly based on post-test results. This study concludes that the “KEUKEU” instructional materials are highly suitable for fourth-grade elementary school students and can enhance their financial literacy